2011
DOI: 10.1159/000331740
|View full text |Cite
|
Sign up to set email alerts
|

Carnosine Prevents Apoptosis of Glomerular Cells and Podocyte Loss in STZ Diabetic Rats

Abstract: Background/Aims: We identified carnosinase-1 (CN-1) as risk-factor for diabetic nephropathy (DN). Carnosine, the substrate for CN-1, supposedly is a protective factor regarding diabetic complications. In this study, we hypothesized that carnosine administration to diabetic rats might protect the kidneys from glomerular apoptosis and podocyte loss. Methods: We examined the effect of oral L-carnosine administration (1g/kg BW per day) on apoptosis, podocyte loss, oxidative stress, AGEs and hexosamine pathway in k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
81
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(87 citation statements)
references
References 52 publications
3
81
1
2
Order By: Relevance
“…Our study is the first Podocytes are inter-connected by slit diaphragms (SDs) that covered the exterior basement membrane surface of the glomerular capillary and maintain the structural integrity of glomerular capillary loops. Recently, several studies have demonstrated that podocyte apoptosis plays a key role in the pathogenesis of DN [19][20][21][22] . Thus, preventing or inhibiting podocyte apoptosis may provide an obvious therapeutic modality for DN treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Our study is the first Podocytes are inter-connected by slit diaphragms (SDs) that covered the exterior basement membrane surface of the glomerular capillary and maintain the structural integrity of glomerular capillary loops. Recently, several studies have demonstrated that podocyte apoptosis plays a key role in the pathogenesis of DN [19][20][21][22] . Thus, preventing or inhibiting podocyte apoptosis may provide an obvious therapeutic modality for DN treatment.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore provide a new mechanism by which carnosine improves the metabolic control in diabetes and protect against the development of complications in diabetes. Even though carnosine shown protective effect in several animal models for complications of diabetes (Pfister et al 2011, Riedl et al 2011, Ansurudeen et al 2012, Yapislar & Aydogan 2012, Brown et al 2014, Peters et al 2014, Menini et al 2015 and strongly suggested to be relevant for diabetes complications in humans (Ahluwalia et al 2011, Kurashige et al 2013) the exact mechanism of action is still unraveled. Here we suggest a potential mechanism by showing that carnosine complexly modulates IGFBP1 by different mechanisms, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Carnosine supplementation mitigates DN, reduces renal vasculopathy, and normalizes vascular permeability in diabetic mice. In streptozotocin-induced, diabetic rats, carnosine treatment prevents apoptosis of glomerular cells and podocyte loss and vascular damage (Riedl et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Both human genetic association studies and animal models suggest a pivotal role for the carnosinecarnosinase system in microvascular complications of diabetes (3,19,33,34,40).…”
mentioning
confidence: 99%
“…Although formal proof for this assumption is still lacking in humans, studies in type 1 and 2 diabetic rodent models revealed that carnosine supplementation caused a later onset of hyperglycemia and a milder course of diabetes with significantly less renal damage (30,31,33,34,36). This beneficial effect can be explained in part by carnosine's physiological and biochemical properties (9).…”
mentioning
confidence: 99%